THE IMPACT OF USING TOKOPEDIA ON PROFITABILITY AND CONSUMER SERVICE - Yusuf, Muhammad; Fitriyani, Zenita Afifah; Abdilah, Adil; Ardianto, Rian; Suhendar, Atep (JURNAL DARMA AGUNG, 2022)
Business actors doubtlessly want to optimize in all parts in order to increase their company's profitability. One thing that must be done is to set up an advertising system based on electronic media, accurately Tokopedia. A system that makes buying and selling transactions simpler for both users and consumers. This article seeks to ascertain the impact of business actors' use of Tokopedia media on resulting profitability, as well as the impact of Tokopedia on consumer convenience when shopping online. This study employed a qualitative strategy in the form of a review article in the field of Tokopedia-based marketing management. Writing scientific articles involves the use of qualitative methods as well as literature studies or library research.